TEACHING WRITING TO EFL STUDENTS: AN ADULT TEACHING REFLECTION - Murwani Ujihanti (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2013)
Teaching writing to low English competence of EFL adult students is challenging. Teachers have big job in training low English competence to meet the high demand writing skills at the job market. This article discusses of the effort to propele the capability of writing in order to be able to meet the requirement of the  job market. First, it describes what ideally writing skills mastered by students. Then, teaching condition and situation are presented to provide overall picture of the EFL situation where the object of the discussion takes place. Finally, suggested solution purposed that is  open for further discussion.